Effect of nozzle parameters on the characteristics of 100% carded cotton jet ring-spun yarns - R.Loganathan, G.Sankaranarayanan, K.Sandeep, K.MuthuvelPandian, P.Sivkumar (Mathematical Statistician and Engineering Applications, 2022)
The effect of single, double and triple air-jet nozzles of different materials, such as brass, aluminum and Teflon, on the characteristics of jet ring - spun yarns has been studied. Regular and jet ring-spun yarns of 19.68 tex, 14.76 tex and 11.81 tex have been produced and then tested for hairiness, tensile and evenness properties. Surface features of all these yarns are compared by scanning electron microscopic studies. It is observed that the jet ring-spun yarns display lower hairiness and higher tenacity. The study further suggests that for achieving a reduction in hairiness and good strength with better evenness properties, the use of single brass nozzle will suffice which would lead to considerable reduction in quantity of air used and enable the piecing to be done more easily in ring frame.